Divergent path: isolating land use and climate change impact on river runoff - Mahmood, Saqib; Khan, Afed Ullah; Babur, Muhammad; Ghanim, Abdulnoor A. J.; Al-Areeq, Ahmed M.; Khan, Daud; Najeh, Taoufik; Gamil, Yaser (Frontiers in Environmental Science, 2024)
Water resource management requires a thorough examination that how land use and climate change affect streamflow; however, the potential impacts of land use changes are frequently ignored. Therefore, the principal goal of this study is to isolate the effects of anticipated climate and land-use changes on streamflow at Indus River Besham, Pakistan using the Soil and Water Assessment Tool (SWAT). The multimodal ensemble (MME) of 11 General Circulation Models (GCMs) under two Shared Socioeconomic Pathways (SSPs) 245 and 585 were computed using Taylor Skill Score (TSS) and Rating Metric (RM). Future land use was predicted using Cellular Automata Artificial Neural Network (CA-ANN). The impacts of climate change and land use change was assessed on streamflow under various SSPs and land use scenarios. To calibrate and validate the SWAT model, the historical record (1991-2013) was divided two parts: calibration (1991-2006) and validation (2007-2013). The SWAT model performed well in simulating streamflow with NSE, R 2 and RSR values during calibration and validation phase are 0.77, 0.79 and 0.48, and 0.76, 0.78 and 0.49 respectively. The results shows that climate change (97.47%) has a greater effect on river runoff than land-use change (2.53%). Moreover, the impacts of SSP585 (5.84-19.42%) is higher incomparison to SSP245 (1.58-4%). The computed impacts of climate and land use changes are recommended to be incorporated in water policies to bring sustainability in the water environment.